Diversity, Equity, and Inclusion in Nursing: The Pathway to Excellence Framework Alignment. Issue 4 (October 2021) - Morrison, Valerie; Hauch, Rodney R.; Perez, Edith; Bates, Melissa; Sepe, Paulette; Dans, Maricon
Abstract : The promotion of diversity, equity, and inclusion (DEI) in nursing is a topic of renewed importance, given the civil unrest following the death of George Floyd and identified disparities in health and health outcomes during the COVID-19 pandemic. Despite its progress, the nursing profession continues to struggle with recruiting and retaining a workforce that represents the cultural diversity of the patient population. The authors completed a review of the literature on DEI in nursing and found a scarcity of studies, and that a limitation exists due to the strength of the evidence examined. This article aims to provide a review of the literature on DEI in nursing, outcomes and strategies associated with organizational DEI efforts, and knowledge on how the American Nurses Credentialing Center Pathway to Excellence® Designation Program framework supports DEI initiatives. The authors further provided recommendations for nurse leaders and a checklist of proposed questions for assessing commitment, culture, and structural empowerment initiatives toward a more diverse, equitable, and inclusive organization.